Can Blood Pressure Be Lowered Safely in Older Adults with Lacunar Stroke? The Secondary Prevention of Small Subcortical Strokes Study Experience. Issue 4 (6th April 2015) - White, Carole L.; Szychowski, Jeff M.; Pergola, Pablo E.; Field, Thalia S.; Talbert, Robert; Lau, Helena; Peri, Kalyani; Benavente, Oscar R.; ,
Abstract : Objectives: To determine safety and tolerability of lowering blood pressure in older adults with lacunar stroke. Design: Cohort study. Setting: The Secondary Prevention of Small Subcortical Strokes (SPS3) Trial, which compared the efficacy of two systolic blood pressure (SBP) targets (<130 mmHg and 130–149 mmHg) for secondary stroke prevention. Participants: Of 3, 020 SPS3 participants, 494 aged 75 and older at baseline were used in these analyses. Measurements: Rates of side effects related to lowering SBP and clinical outcomes, including stroke recurrence and vascular death, were examined. Results: Older participants achieved SBP levels similar to those of younger participants (mean SBP of 125 mmHg and 137 mmHg in lower and higher SBP target groups, respectively). At least once during the approximately 3.5 years of follow‐up, 21% reported dizziness, and 15% reported lightheadedness when standing; the only significant difference between the younger and older groups was unsteadiness when standing (23% vs 32% respectively, P < .001). There was no difference according to treatment group. In younger adults, recurrent stroke was less likely in the lower than the higher SBP group (hazard ratio (HR) = 0.77, 95% confidence interval (CI) = 0.59–1.01) but not in older participants (HR = 1.01, 95% CI = 0.59–1.73), although the interaction was not significant ( P = .39). The lower SBP target was associated with a significant reduction in vascular death in older participants (HR = 0.42, 95% CI = 0.18–0.98), with a significant interaction between age and SBP group ( P = .049). Conclusion: Except for unsteadiness when standing, there was no difference according to age in individuals with lacunar stroke with respect to side effects potentially related to lowering blood pressure. Although the lower SBP target was not associated with lower likelihood of recurrent stroke, these exploratory analyses suggested a possible benefit related to vascular death.